The book of longings - Kidd, Sue Monk (New York : Viking, 2020)
"Raised in a wealthy family with ties to the ruler of Galilee, Ana is rebellious and ambitious, with a brilliant mind and a daring spirit. Ana is expected to marry an older widower, a prospect that horrifies her. An encounter with eighteen-year-old Jesus changes everything. Their marriage evolves with love and conflict, humor and pathos in Nazareth, where Ana makes a home with Jesus, his brothers, and their mother, Mary. Ana's pent-up longings intensify amid the turbulent resistance to Rome's occupation of Israel, partially led by her brother, Judas."--
Bibliographic references.
Keywords: Jesus Christ -- Family -- Fiction; Women authors -- Fiction; Self-realization in women -- Fiction; Feminism -- Fiction; Man-woman relationships -- Fiction; Courage -- Fiction; Biographical fiction; Historical fiction; Bible fiction